PEGylation of silica coated hydroxyapatite nanoparticles for targeted drug delivery - Tang, Andrew BingXiang. (2009)
Hydroxyapatite (HA, Ca10(PO4)6(OH)2) was synthesised using the double inverse microemulsion (DIME) method. It was then surfaced modified with silica. Silica was then coated on the HA particles using a method based on the Stober process. Poly(ethylene glycol) methyl ether (PEGME, Mw= 5000) was first linked to 3-(triethoxysilyl)propyl isocyanate (IPTES) before PEGylation with the silica coated HA. IPTES was used as a linker to enhance the bonding strength of PEGME to silica. The entire project was done at room temperature. Modes of characterization used include Field-Emission Scanning Electron Microscope (FESEM), Fourier Transform Infrared Spectroscopy (FTIR), Thermogravimetric Analysis (TGA) and the Nanosizer and Zeta Potential. Results show that the silica coating on HA and the synthesis of the IPTES-PEGME monomer were successful. PEGylation was partially successful.